Pengaruh Terapi Bekam terhadap Penurunan Tekanan Darah pada Penderita Hipertensi di Rumah Sehat Ibnu Sina Palembang - Mardiah Mardiah; Dedi Pahrul; Lily Marleni; Adi Saputra; Ematiyana Ematiyana (Jurnal Surya Medika (JSM), 2022)
The prevalence of hypertension in 2015 was 34.1%, and in 2018 it increased by 34.1%. Hypertension was caused by an increase in blood pressure. Prevention of hypertension can be done by nonpharmacological treatment with cupping therapy. This study aimed to determine the effect of cupping therapy to decrease blood pressure of patients with hypertension at Ibnu Sina clinic Palembang. The quantitative pre-experimental research with a one-group pretest-posttest design approach. The sample of this study was 45 patients with hypertension. The study was done at the Ibnu Sina clinic on the 20th –30th of June 2021. The results showed that the systolic blood pressure before cupping therapy was 153.20 mmHg and the average diastolic blood pressure was 98.60 mmHg. In contrast, after cupping therapy, the results showed that the mean systolic blood pressure was 98 .60 mmHg and the mean diastolic pressure was 91.20 mmHg. Based on the statistical test, it was found that the p-value was 0.000. it means that systolic blood pressure was affected before and after cupping therapy. It is hoped that the results of this study can improve services for patients with hypertension-related to cupping therapy in lowering blood pressure and can provide knowledge for therapists about the effect of cupping therapy on decreasing blood pressure in patients with hypertension. The sample was 18 respondents who were postoperative appendectomy patients at the AR Bunda Prabumulih Hospital. This research was conducted in 2021. The observation sheet was used to collect the data. The research data were analyzed using the Wilcoxon Signed Ranks Test. Based on the results of data analysis with the Wilcoxon test, it showed a significant effect between the average pain scale before and after giving back massage with a p-value of 0.000 < (0.05) Ha accepted. In other words, it can be concluded that there was an effect of back massage on the pain scale in postoperative appendectomy patients at the AR Bunda Prabumulih Hospital. Based on this research, it is recommended for health practitioners to apply nonpharmacological therapy techniques and pharmacological treatment; one of those techniques is back massage, which effectively reduces pain scale.